Investor reaction to strategic emphasis on earnings numbers: An empirical study - M. Shibley Sadique; M. Arifur Rahman (Contemporary Economics)
We analyze the earnings information and stock prices of S&P500 firms and find that investors following S&P500 stocks (i) respond more to pro forma earnings than to GAAP earnings, (ii) respond to an emphasis on pro forma earnings, and (iii) are fixated on pro forma earnings. We provide the first direct evidence that a strategic emphasis on earnings numbers may affect return volatility. Further, our results do not support the argument that a larger investor response to Street earnings might be driven by large differences between the Street numbers and GAAP numbers.